Cardinal Stefan Wyszynski as the defender of truth, freedom and justice in the period of communist enslavement o - Buczek, Jerzy (Studia Theologica Varsaviensia, 2019)
Cardinal Wyszyński was a defender of every individual, family, nation and Church during the time of communist enslavement of Poland. He was an ardent defender of the truth with regard to human being and its dignity, he constantly emphasized the significance of respecting basic rights and obligations of men, and strongly demanded the observance of these rights when the state violated them. Furthermore, he was radical defender of the freedom of human persons, families, nation and the Church, indicating that only in freedom can they truly develop and fulfill their vocation and goals. He constantly reminded us of the need for justice made in the spirit of love with regard to every individual, family and nation. He clearly defined the tasks and duties of the state and the Church in relation to every human person that should be regarded as the highest value in the world, as well as towards families that are to be considered the cradle of the nation, and towards the nation that he regarded as a family of families sui generis. Additionaly he emphasized that the Church has a unique role to perform in relation to these communities, bringing into their existence not only the supernatural dimension, sanctifying God’s grace, salvation, but also the natural dimension consisting in the care of the Church for the national raison d’etat. Last but not least, in his view, the Church must be free and independent in its activities to be able to perform its religious and social role properly. The Primate indicated the need for cooperation between the state and the Church for the benefit of man, family and nation. When the communist state did not fulfill its role and acted against the rights of citizens, especially believers, against families and nation, he radically opposed these actions, demanding respect for dignity, rights, truth, freedom and justice with regard to every human person, family and family of families – that is the nation.